Effect of pocket compression device on pocket hematoma after cardiac implantable electronic device implantation - Narawudt Prasertwitayakij; Jakkapun Yanyongmathe; Natnicha Pongbangli; Teerapat Nantsupawat; Siriluck Gunaparn; Cheeranun Pisespongsa; Chanya Tawaditap; Arintaya Phrommintikul; Wanwarang Wongcharoen (Scientific Reports)
Abstract Pocket hematoma is a common and serious complication following cardiac implantable electronic device (CIED) implantation, contributing to significant morbidity and mortality. This study aimed to evaluate the efficacy of a novel pocket compression device in reducing pocket hematoma occurrence. We enrolled 242 patients undergoing CIED implantation, randomly assigning them to receive either the novel compression vest with a pressure cuff or conventional sandbag compression. Pocket hematomas were categorized as grade 1 (mild), grade 2 (moderate), or grade 3 (severe, requiring intervention or prolonged hospitalization). The primary endpoint, incidence of pocket hematoma 24 h post-procedure, did not significantly differ between the two groups (26.7% vs. 19.7%, p = 0.224). Rates of grade 2 hematoma were similarly low and comparable (2.5% vs. 0.8%, p = 0.368), with no grade 3 hematomas observed. Skin reactions and patient comfort were similar between groups. The sole predictor for hematoma occurrence was current oral anticoagulation use. In conclusion, our study found a low incidence of clinically significant pocket hematomas. The novel pocket compression device showed comparable efficacy to conventional methods, suggesting it as a viable alternative for reducing post-procedural complications without additional adverse effects. Trial registration number: The study was registered in the Thai Clinical Trials Registry (TCTR) at https://www.thaiclinicaltrials.org/ , with the identification number TCTR20230913005, date of first trial registration 13/09/2023.